Coagulation Changes with intravenous Administration of Fat after Blocking the RES - Kommerell, B; Barth, P; Pfleiderer, Th (Thrombosis and Haemostasis, 1966)
Rabbits were treated in 3 groups : Group A received 20 ml/kg Lipofundin, group B received 150 mg/kg india ink and 20 ml/kg Lipofundin, group C received 150 mg/kg india ink and 20 ml/kg isotonic glucose. Group A and B showed a decrease of activity of the factors II, V, VII, serumcomplex and a decrease of the platelet count. The changes were more pronounced in group B and 6 of 8 animals of this group died after the infusion. In group A only 1 animal died. All controll animals (group C) survived. There were no significant changes in the coagulation system in group C. The contact factors showed an activation in group B, little activation in group A and inconsistent activation in group C. In vitro india ink was able to produce a moderate activation of the contact system. The high death rate after administration of india ink and fat is thought to be due to a consumptive coagulopathy.